Analisis Nilai Tambah Dan Keuntungan Pengolahan Ekoenzim Menjadi Sabun Di Desa Kawatak Kecamatan Langowan Selatan Kabupaten Minahasa - Siburian, Erinda Ully Artha; Loho, Agnes Estephina; Pakasi, Caroline Besty Diana (Sam Ratulangi University, 2024)
This research aims to determine the added value and profitability of ecoenzymes when used to make dish soap and bath soap. The study was conducted over a period of three months, from January to March 2024, covering everything from preparation to the writing of the research report. The research took place at the DSY Monastery in Kawatak Village, Langowan Selatan District, Minahasa Regency. Data were collected through primary sources, including observations, interviews, and documentation related to the soap-making process, costs incurred, product pricing, and raw materials used. Secondary data were obtained from supporting sources, including information about waste products and relevant institutions providing necessary data. The data analysis involved identifying issues using value-added analysis. The results indicate that the production of dish soap yields an added value of IDR10,116 per production cycle, while bath soap production yields an added value of IDR79,539 per cycle. The profit margin for dish soap production is 6.316%, whereas for bath soap production, it is 73.20%. The highest profit margin is achieved in bath soap production at 73.20%.